In vitro antioxidant activity of Bixa orellana (Annatto) Seed Extract - Modupeola Abayomi,Amusa S. Adebayo,Deon Bennett,Roy Porter, and Janet Shelly-Campbell (Journal of Applied Pharmaceutical Science, 2014)
The seeds of Bixa orellana (Annatto, family Bixaceae), have been used in food coloring for over 50 years. With the aim of introducing its extracts as pharmaceutical colorant, there is the need to investigate the biological and pharmacological activities of the extract. This study was designed to develop extraction protocols for annatto coloring fraction with potential for pharmaceutical application and evaluate the antioxidant activity of the extracts in vitro. Powdered seed material was extracted using acid-base protocols and the crystals obtained were washed with deionized water, oven-dried for about 12 hours at 45 °C and stored in air-tight containers. The in vitro antioxidant activity was tested via 2,2-diphenyl-1- picrylhydrazyl (DPPH) radical scavenging activity and iron (III) oxide reducing power using ascorbic acid (vitamin C) as a reference standard. The free radical scavenging activity of annatto extract ranged from 5.5 % to 48.9 % relative to ascorbic acid (2.9 % to 41.5 %) at respective concentrations between 0.25 and 2.5 μg/ml. Similarly, iron (III) oxide reducing power shows good linear concentration-dependent relation (R2 = 0.9986) comparable with ascorbic acid (R2 = 0.9934). Results generally indicated that Bixa orellana seed extract is a potential source of antioxidants of natural origin.
Keywords: In-vitro, Antioxidant, Bixa orellana, DPPH, Ferric